A Fluoride‐Ion‐Conducting Solid Electrolyte with Both High Conductivity and Excellent Electrochemical Stability. Issue 5 (27th November 2021) - Wang, Jinzhu; Hao, Jipeng; Duan, Chaomin; Wang, Xinchao; Wang, Kai; Ma, Cheng
Abstract: Solid‐state fluoride‐ion batteries (FIBs) circumvent multiple formidable bottlenecks of lithium‐ion batteries, but their overall performance remains inferior due to the absence of appropriate solid electrolytes. Presently the conductivity of most solid electrolytes for FIBs is too low to enable room‐temperature cycling, while the few sufficiently conductive ones only allow for very low discharge voltages because of the narrow electrochemical stability window (ESW). Here, high room‐temperature conductivity and a decent ESW are simultaneously achieved by designing a solid electrolyte CsPb0.9 K0.1 F2.9 . Its room‐temperature conductivity is 1.23 ×  10 −3  S cm −1, comparable to the most conductive system reported so far (PbSnF4, 5.44 ×  10 −4 –1.6 ×  10 −3  S cm −1 ), but the ESW is several times broader. With these appealing characteristics simultaneously achieved in the solid electrolyte, a cell with much higher voltages than other room‐temperature‐operable solid‐state FIBs in literature is successfully constructed, and stably cycled at 25 °C for 4581 h without considerable capacity fade. Abstract : Solid‐state F‐ion‐batteries possess high theoretical energies which could surpass that of Li‐air batteries, but presently they can barely operate at room temperature due to the absence of appropriate solid electrolytes. Here, an F‐ion‐conducting solid electrolyte with both high ionic conductivity and excellent electrochemical stability is discovered. This material enables room‐temperature, long‐term cycling of solid‐state F‐ion‐batteries for the first time.